ANALISIS KELAYAKAN USAHA KERUPUK PEYEK DI KABUPATEN PELALAWAN - Manuel Paul; Maulida Yusni; Pailis Armas Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to see the feasibility of establishing a peyek cracker business in Pelalawan Regency in terms of marketing, supply of raw materials, socio-economic and financial aspects. This research was conducted in Pelalawan Regency. The object of research is small cracker crackers in Pelalawan district. The data were analyzed by descriptive analysis to see the feasibility of the Peyek cracker business in terms of marketing, socio-economic and quantitative data analysis to see the feasibility of the Peyek cracker business, finance by using Net Present Value, Benefit Cost Ratio, Internal Rate of Return. Results From research conducted on 25 respondents, it is known that the feasibility of Peyek crackers for business fans from the marketing aspect is included in the feasible category. In terms of raw materials, the establishment of the Peyek cracker business is feasible to be determined. From the socio-economic aspect, the fried banana fan business is feasible to open and generate profits, the Peyek cracker business in the financial aspect of the Net Present Value of Rp 97,505,378>0, then the Peyek cracker business is feasible to be established. Value Benefit Cost Ratio is 1.23>1, then Peyek cracker business is feasible to be established. The value of the Internal Rate of Return is 46.88%>12%, so the Peyek cracker business is feasible to be established in Pelalawan district.Keywords : feasibility business, peyek cracker